Los impactos del cambio climático al cacao en centro américa: Presentación en II Foro Centroamericano de cacao - San Pedro Sula - Zelaya, Carlos; Lundy, Mark M.; Bunn, Christian (2016)
What is the projected impact of climate change on cocoa value chains globally and in Central America. What can be done to improve the resilience of these production systems to the projected impact of climate change?